SALES SYSTEM INFORMATION AT THE SALDAS JAKARTA MEAT SHOP USING THE SWOT METHOD - Fajar Masya; Syarief Hidayatullah; Martin Ronaldo Yosef; Anrico Ananda Putra (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Saldas Jakarta Meat Shop is a business that is engaged in selling frozen meat and frozen food consisting of beef, mutton, chicken, fish, and frozen processed products with well-known brands. Saldas Jakarta Meat Shop has problems in the sales process that only relies on offline transactions. Then the recording of product purchase orders, product sales reports, product stock reports, to income reports are still done manually, which results in report documentation not being properly structured so that business owners and employees experience difficulties during the process of finding the required data. The information system for selling frozen meat and frozen food is expected to help overcome these problems with the aim of increasing effectiveness and efficiency in managing business operations. Seeing the situation and conditions in the Saldas Meat Shop business in Jakarta, business process analysis and system analysis were carried out using the SWOT method and system development using the Waterfall method.